Into the void - Lebbon, Tim (Dawn of the Jedi, 2013)
A stand-alone tie-in to the successful comic book series, Star Wars: Dawn of the Jedi reveals the origins of the Jedi Order on the remote world of Tython, where ancient philosophers and scientists share their mystical knowledge of the Force while colonizing a dangerous new homeworld.